Kinetics of macroradicals propagation and decay in polymeric matrix of 1,6-hexanediol diacrylate - Medvedevskikh, Yuriy; Khovanets, Galyna; Kytsya, Andriy; Yevchuk, Iryna (Publishing House of Lviv Polytechnic National University, 2007)
ЕПР-методом досліджена залежність концентрації акрилатних макрорадикалів у полімерній матриці 1,6-гександіолдиакрилату від часу в температурному інтервалі 318-353 K. Встановлено, що експериментальні дані не лінеаризуються в координатах рівняння реакції другого порядку, що відповідає бімолекулярному механізму загибелі макрорадикалів. Висловлено припущення, що ефект зниження константи швидкості бімолекулярної загибелі макрорадикалів у часі пов’язаний з їхнім ростом в реакції продовження ланцюга. Одержане на цій основі кінетичне рівняння задовільно описує експериментальні дані, що дозволило кількісно оцінити такі параметри, як константи швидкостей росту і обриву ланцюга в полімерній матриці, коефіцієнт дифузії макрорадикалів і характеристичний час сегментального руху. Dependence of acrylate macroradicals concentration in polymeric matrix of 1,6-hexanediol diacrylate on time within temperature range of 318–353 K has been investigated by means of ESR-spectroscopy. It has been established that experimental data do not linearize in coordinates of the equation of the second order reaction, that coordinates with bimolecular mechanism of macroradicals decay. It has been suggested, that the effect of decreasing the rate constant of bimolecular macroradicals decay in time is related with their propagation in chain propagation reaction. Kinetic equation obtained on this basis describes experimental data satisfactorily, that allowed to estimate quantitatively such parameters as the rate constants of chain propagation and termination in polymeric matrix, diffusion coefficient of macroradicals and characteristic time of segmental movement.
Кінетика росту і загибелі макрорадикалів у полімерній матриці 1,6-гексан діолдиакрилату
Keywords: полімернаматриця; макрорадикал; ріст ланцюга; обрив ланцюга; дифузія; сегментальний рух; polymeric matrix; macroradical; chain propagation; chain termination; diffusion; segmental movement